Unusual causes of obstruction to transplant ureter - Shivde Subodh; Date Jaydeep; Dighe Tushar; Joshi Pankaj (Saudi Journal of Kidney Diseases and Transplantation, 2010)
Surgical complications remain a significant clinical problem following renal trans-plantation. Ureteral obstruction following transplantation is not uncommon. Persistent obstruc-tion of the ureterovesical anastomosis is the most common urologic complication. Obstruction occurring beyond the first post operative month remains frequent (2-7.5%) and mostly related to ureteral stenosis. We report here a case of Ureteral stenosis due to an unusual cause and review the literature.